2015
DOI: 10.1038/nature14287
|View full text |Cite
|
Sign up to set email alerts
|

Two disparate ligand-binding sites in the human P2Y1 receptor

Abstract: In response to adenosine 5′-diphosphate, the P2Y1 receptor (P2Y1R) facilitates platelet aggregation, and thus serves as an important antithrombotic drug target. Here we report the crystal structures of the human P2Y1R in complex with a nucleotide antagonist MRS2500 at 2.7Å resolution, and with a non-nucleotide antagonist BPTU at 2.2Å resolution. The structures reveal two distinct ligand binding sites, providing atomic details of P2Y1R’s unique ligand binding modes. MRS2500 recognizes a binding site within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
334
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 319 publications
(348 citation statements)
references
References 38 publications
(48 reference statements)
14
334
0
Order By: Relevance
“…To explore this possibility we selected a Class A G‐protein couple receptor (GPCRs) depositing onto the stage 0.4 nmoles of P2Y 1 , responsible for platelet aggregation and a key target for anti‐thrombotic therapy 27. After recording a native DESI spectrum in its apo form we added a cocktail of antagonists/agonists designed to target related GPCRs (Figure 3 d,e and Table S1).…”
mentioning
confidence: 99%
“…To explore this possibility we selected a Class A G‐protein couple receptor (GPCRs) depositing onto the stage 0.4 nmoles of P2Y 1 , responsible for platelet aggregation and a key target for anti‐thrombotic therapy 27. After recording a native DESI spectrum in its apo form we added a cocktail of antagonists/agonists designed to target related GPCRs (Figure 3 d,e and Table S1).…”
mentioning
confidence: 99%
“…Interestingly, previous mutation studies on P2Y 1 have indicated that some antagonists may bind deeper in the receptor at a site analogous to the P2Y 12 receptor (Ref. 40 and references cited therein). The most unexpected finding of the P2Y 1 structure is the binding site of the non-nucleotide antagonist BPTU, which was found to bind on the outside of the receptor on the lipid interface between TM1, TM2, and TM3 (Fig.…”
Section: Key Features Of Gpcr Structures Relevant To Drug Discoverymentioning
confidence: 99%
“…The structure of the P2Y 1 receptor, another platelet receptor involved in platelet aggregation, has also revealed multiple binding sites (40). The nucleotide antagonist MRS2500 binds to a site at the top of the transmembrane domain between TM6 and TM7 but also involving the N terminus and extracellular loop 2.…”
Section: Key Features Of Gpcr Structures Relevant To Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…The fusion proteins themselves are highly crystalizable and feature N and C termini at the right distance for their insertion into GPCR loops without resulting in a significant distortion of the transmembrane bundle . These fusion proteins are typically T4L Jaakola et al, 2008;Wu et al, 2010) or a thermostabilized apocytochrome (b 562 RIL) Liu et al, 2012;Zhang et al, 2014), but more recently other proteins have also been used successfully as ICL3 fusions, such as the catalytic domain of Pyrococcus abyssi glycogen synthase in the orexin 2 receptor (OX 2 R) (Yin et al, 2015), or rubredoxin in C-C chemokine receptor type 5 (CCR5) (Tan et al, 2013) and the P2Y 1 receptor (Zhang et al, 2015a) (Supplemental Table 1). …”
Section: Molecular Biology Approaches To Facilitate Gpcr Crystallographymentioning
confidence: 99%